Variation in the IL1B, TNF and IL6 genes and individual susceptibility to prosthetic joint infection - Stahelova, Anna; Mrazek, Frantisek; Smizansky, Matej; Petrek, Martin; Gallo, Jiri (BMC immunology, 2012)
BACKGROUND: Prosthetic joint infection (PJI) is an important failure mechanism of total joint arthroplasty (TJA). Here we examine whether the particular genetic variants can lead to increased susceptibility to PJI development. RESULTS: We conducted a genetic-association study to determine whether PJI could be associated with functional cytokine gene polymorphisms (CGP) influencing on innate immunity response. A case-control design was utilized and previously published criteria for PJI were included to distinguish between cases and control subjects with/without TJA. Six single nucleotide polymorphisms (SNPs) located in the genes for interleukin-1beta (SNP: IL1B-511, +3962), tumour necrosis factor alpha (TNF-308, -238) and interleukin-6 (IL6-174, nt565) were genotyped in 303 Caucasian (Czech) patients with TJA (89 with PJI / 214 without PJI), and 168 unrelated healthy Czech individuals without TJA. The results showed that carriers of the less common IL1B-511*T allele were overrepresented in the group of TJA patients with PJI (69%) in comparison with those that did not develop PJI (51%, p = 0.006, p(corr) = 0.037) and with healthy controls (55%, p = 0.04, p(corr) = N.S.). There was no significant difference in the distribution of the remaining five investigated CGPs and their haplotypes between groups. CONCLUSION: A functional variant of the gene encoding for IL-1beta was preliminarily nominated as a genetic factor contributing to the susceptibility to PJI. Our results should be independently replicated; studies on the functional relevance of IL1B gene variants in PJI are also needed.
Keywords: Young Adult; DNA Mutational Analysis; genetické asociační studie; Male; Genetic Predisposition to Disease; Tumor Necrosis Factor-alpha; genetická predispozice k nemoci; mladý dospělý; polymorfismus genetický; infekce spojené s protézou; artroplastika; Genetic Association Studies; Interleukin-6; Adult; Case-Control Studies; dospělí; interleukin-1beta; mužské pohlaví; Polymorphism, Genetic; mutační analýza DNA; lidé; ženské pohlaví; studie případů a kontrol; protézy kloubů; interleukin-6; Humans; Prosthesis-Related Infections; Interleukin-1beta; TNF-alfa; Joint Prosthesis; Female; Arthroplasty